Clinical Performance of a Dedicated Urine-Based Assay for the Detection of Human Papillomavirus and Cervical Intraepithelial Neoplasia - Zhao Y; Zhao L; Wang Z; Cui S; Ren C; Yang L; Bai Y; Zhu Y; Xie J; Li Y; Wu X; Feng J; et al. (Dove Medical Press, 2023)
Yun Zhao,1,* Lijun Zhao,1,* Zhaohuang Wang,1 Shuhui Cui,1 Chenchen Ren,2 Li Yang,2 Yang Bai,2 Yuanhang Zhu,2 Jingyan Xie,3 Yujuan Li,3 Xiaoqing Wu,3 Jing Feng,3 Shanqing Man,4 Longmei Huang,4 Xiaoqi Li,4 Xiaotian Yu,4 Jianliu Wang1 1Department of Obstetrics and Gynecology, Peking University People's Hospital, Beijing, People's Republic of China; 2Department of Obstetrics and Gynecology, The Third Affiliated Hospital of Zhengzhou University, National Clinical Research Center for Obstetrics and Gynecology, Zhengzhou Key Laboratory of Cervical Disease, Zhengzhou Key Laboratory of Endometrial Disease Prevention and Treatment, Zhengzhou, Henan, People's Republic of China; 3Department of Obstetrics and Gynecology, Nanjing First Hospital, Nanjing Medical University, Nanjing, Jiangsu, People's Republic of China; 4Hangzhou New Horizon Health Technology Co. Ltd, Hangzhou, Zhejiang, People's Republic of China*These authors contributed equally to this workCorrespondence: Jianliu Wang, Department of Obstetrics and Gynecology, Peking University People's Hospital, 11 Xizhimen South Street, Xicheng District, Beijing, 100044, People's Republic of China, Tel +8618901086568, Email wangjianliu1203@163.comObjective: The objective of this study is to assess the clinical performance of a urine-based high-risk human papillomavirus (hrHPV) test for the detection of cervical intraepithelial neoplasia grade 2 or higher (CIN2+).Methods: Between September and December 2021, women aged 20 to 65 years referred to colposcopy clinic were prospectively recruited at three clinical centers in China. Paired urine and cervical specimens from all enrolled women were obtained for hrHPV DNA fluorescence quantitative PCR test. The results of liquid-based cytology (LBC), colposcopy and diagnostic biopsies were collected. We evaluated the sensitivity and specificity for CIN and assessed the agreement/kappa value.Results: A total of 732 women (median age, 40 years) with valid results were included in the study, and 130 (17.8%) women were histologically confirmed as CIN2+. The sensitivity of urine and cervical test for CIN2+ and CIN3+ were 87.69% and 85.45%, respectively. The specificity of urine test performed better than cervical test in women with